2004
DOI: 10.1109/joe.2004.836998
|View full text |Cite
|
Sign up to set email alerts
|

Internal Tide and Nonlinear Internal Wave Behavior at the Continental Slope in the Northern South China Sea

Abstract: The sea floor at the site is gradually sloped at depths less than 90 m, but the deeper area is steppy, having gradual slopes over large areas that are near critical for diurnal internal waves and steep steps between those areas that account for much of the depth change. Large-amplitude nonlinear internal gravity waves incident on the site from the east were observed to change amplitude, horizontal length scale, and energy when shoaling. Beginning as relatively narrow solitary waves of depression, these waves c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
168
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(181 citation statements)
references
References 28 publications
12
168
0
1
Order By: Relevance
“…Thus, it is important to understand their shoaling dynamics. Observations have shown that shoaling ISWs exhibit significant structural changes Duda et al, 2004;Orr and Mignerey, 2003;Ramp et al, 2004). Lien et al (2012Lien et al ( , 2014 observed waves in the vicinity of the ASIAEX experiments with recirculating cores.…”
Section: K G Lamb and A Warn-varnas: Shoaling Internal Solitary Wavesmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, it is important to understand their shoaling dynamics. Observations have shown that shoaling ISWs exhibit significant structural changes Duda et al, 2004;Orr and Mignerey, 2003;Ramp et al, 2004). Lien et al (2012Lien et al ( , 2014 observed waves in the vicinity of the ASIAEX experiments with recirculating cores.…”
Section: K G Lamb and A Warn-varnas: Shoaling Internal Solitary Wavesmentioning
confidence: 97%
“…During the ASIAEX experiment, intensive measurements of shoaling ISW trains over the continental shelf off China were undertaken Duda et al, 2004;Orr and Mignerey, 2003;Ramp et al, 2004). Ramp et al (2004) reported on observations from a series of moorings spanning depths of 350-72 m illustrating the evolution of these waves as they shoaled.…”
Section: K G Lamb and A Warn-varnas: Shoaling Internal Solitary Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In the open ocean, typically, the waves are highly nonlinear and may attain very large amplitudes. [5][6][7] It is well known that at such large amplitudes, ISWs of depression (elevation) may exhibit trapped cores if the density gradient at the surface (bottom) of the water column is finite (and waves are supported in which the local horizontal fluid velocity exceeds the wave speed). As well as in the ocean, 8,9 waves of this type have been observed in the atmosphere, 10-12 the laboratory, 13,14 and in theoretical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The wide-spread appearance of packets of long internal waves in the shallow, stratified waters of the coastal ocean and lakes is firmly established (Osborne and Burch, 1980;Apel et al, 1985;Scotti and Pineda, 2004;Ostrovsky and Stepanyants, 1989;Stanton and Ostrovsky, 1998;Antenucci et al, 2000;Duda et al, 2004;Helfrich and Melville, 2006). These long-wave packets in many contexts are decidedly nonlinear, containing waves with amplitudes that are equal to and greater in magnitude than the controlling length scale of the problem, which is typically the scale of the uppermixed layer depth.…”
Section: Preliminary Considerationsmentioning
confidence: 99%